Development of Money Mobile Game-Based Learning Application - YIM, PEI CHEN; Ahmad Shaubari, Ezak Fadzrin (Applied Information Technology And Computer Science, 2024)
Money is a medium of transaction in the form of banknotes and coins. The traditional way to teach about money in math class at a primary school is through textbooks or other written material, which is less interactive. Therefore, a mobile application, namely Simple Money is developed on the Android platform to help kids learn money. The target users for this project are Year 1 primary school students. This application was implemented by using 2D game-based learning approach and developed by using Multimedia Mobile Content Development (MMCD) methodology. This application is expected to assist target user to recognize the pattern and value of money, convert money using different combinations of coins or banknotes, and add and subtract the value of money. The result from user testing shows a higher acceptance level with an average percentage of 77.42%. More games and levels and reward systems can be improved in the future.